ANALISIS KESEDIAAN MASYARAKAT DALAM MEMBAYAR (WILLINGNESS TO PAY) TARIF PDAM KOTA KENDARI - Syamsir Nur; Arifin Arifin (Universitas Muhammadiyah Kendari, 2019)
This study aims to estimate the value of Willingness to Pay PDAM rates at Green Anggoeya Resort Kendari and the Affecting Factors. The type of data used is primary data obtained from the PDAM water user community, and secondary data obtained from the office of PDAM Tirta Anoa Kendari. The method used is the Willingness to Pay (WTP) approach using the Contingent Valuation Method (CVM) analysis method. The results showed that the average WTP (Willingness to Pay) value of the community in paying for PDAM water is IDR 6,210.14 per m3 for each family head (KK), this value is lower than the current PDAM rates of IDR 6,500 /m3. The total value of the PAPs is IDR 1,620,847.83 per month so that the amount of willingness to pay PDAM rates at Green Anggoeya Resort Kendari in one year is IDR 19,450,173.96. The factors that influence WTP are the Water Quality and Service of PDAM obtained by PDAM customers in Kendari City.